2017
DOI: 10.4315/0362-028x.jfp-17-035
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Antimicrobial Combinations Inhibit and Inactivate Listeria monocytogenes in Neutral and Acidic Broth Systems

Abstract: The use of antimicrobial compounds can be an effective approach to control Listeria monocytogenes in ready-to-eat foods, but it can also be limited by cost, restrictions on concentrations in foods, and potential changes to organoleptic properties. Combinatorial approaches that produce additive or synergistic effects allow for reductions in individual antimicrobial concentrations while achieving the same level of control. The present study determined the MIC and MBC of an antimicrobial compound when used alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
2
22
1
Order By: Relevance
“…According to US Food and Drug Administration (FDA) guidance on the control of L. monocytogenes in ready-to-eat foods, a listeristatic formulation that combines one or more antimicrobial substances is generally considered to be effective as a process control if growth studies that include samples at various points during product shelf life show an increase of <1 log 10 cycle over 2 or more time intervals (e.g., days, weeks, and so on, based on sampling plan) in the number of L. monocytogenes during replicate trials with the food of interest (FDA, 2017b). Several antimicrobials generally recognized as safe (GRAS) by the FDA including caprylic acid (CA; FDA, 2015), hydrogen peroxide (HP; FDA, 2015), lauric arginate (LAE;FDA, 2005a,b), and ε-polylysine (EPL; FDA, 2011) have demonstrated efficacy in controlling L. monocytogenes under varying experimental conditions (Luchansky et al, 2005;Amrouche et al, 2010;Kozak et al, 2017), including applications in milk (Romanova et al, 2002;Geornaras et al, 2007;Ma et al, 2013) and cheese (Soni et al, 2010;Gadotti et al, 2014). Limited data are available on the efficacy of sodium caprylate (SC) against L. monocytogenes (Kozak et al, 2017), but several fatty acid derivatives including SC have demonstrated antimicrobial effects against gram-positive bacteria (Kabara et al, 1972;Nair et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to US Food and Drug Administration (FDA) guidance on the control of L. monocytogenes in ready-to-eat foods, a listeristatic formulation that combines one or more antimicrobial substances is generally considered to be effective as a process control if growth studies that include samples at various points during product shelf life show an increase of <1 log 10 cycle over 2 or more time intervals (e.g., days, weeks, and so on, based on sampling plan) in the number of L. monocytogenes during replicate trials with the food of interest (FDA, 2017b). Several antimicrobials generally recognized as safe (GRAS) by the FDA including caprylic acid (CA; FDA, 2015), hydrogen peroxide (HP; FDA, 2015), lauric arginate (LAE;FDA, 2005a,b), and ε-polylysine (EPL; FDA, 2011) have demonstrated efficacy in controlling L. monocytogenes under varying experimental conditions (Luchansky et al, 2005;Amrouche et al, 2010;Kozak et al, 2017), including applications in milk (Romanova et al, 2002;Geornaras et al, 2007;Ma et al, 2013) and cheese (Soni et al, 2010;Gadotti et al, 2014). Limited data are available on the efficacy of sodium caprylate (SC) against L. monocytogenes (Kozak et al, 2017), but several fatty acid derivatives including SC have demonstrated antimicrobial effects against gram-positive bacteria (Kabara et al, 1972;Nair et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial strains, growth conditions, and inoculum Preparation A cocktail was prepared as previously described (Kozak et al, 2017) using eight L. monocytogenes strains associated with outbreaks linked to soft cheeses or isolated from cheese processing environments ( Table 1). The cocktail was serially diluted in Butterfield's phosphate buffer (BPB), pelleted through centrifugation (30 min, 4,000 g at 4°C) (Thermo Scientific Sorvall Legend X1R, ThermoFisher Scientific, Waltham, MA, USA), and resuspended in BPB to attain ~7 log CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…LAE can bind to anionic biopolymers naturally present within the mouth leading to a perceived bitterness or astringency, but the impact of complexation interactions (i.e., LAE and chitosan) on the sensory attributes of LAE (i.e., ability to cause astringency) are also not known (Bonnaud et al, 2010). As an alternative, the use of combinations of antimicrobials that work additively or synergistically to inhibit or inactivate L. monocytogenes can potentially enhance antimicrobial efficacy without increasing individual usage concentrations (Kozak et al, 2017).…”
Section: Antimicrobial Activity Of Chitosan Coating With Acslmentioning
confidence: 99%
See 2 more Smart Citations